Plasma Cell-Free DNA Methylomics of Bipolar Disorder With and Without Rapid Cycling - Ho, Ada Man-Choi; Winham, Stacey J.; McCauley, Bryan M.; Kundakovic, Marija; Robertson, Keith D.; Sun, Zhifu; Ordog, Tamas; Webb, Lauren M.; Frye, Mark A.; Veldic, Marin (Frontiers in Neuroscience, 2021)
Rapid cycling (RC) burdens bipolar disorder (BD) patients further by causing more severe disability and increased suicidality. Because diagnosing RC can be challenging, RC patients are at risk of rapid decline due to delayed suitable treatment. Here, we aimed to identify the differences in the circulating cell-free DNA (cfDNA) methylome between BD patients with and without RC. The cfDNA methylome could potentially be developed as a diagnostic test for BD RC. We extracted cfDNA from plasma samples of BD1 patients (46 RC and 47 non-RC). cfDNA methylation levels were measured by 850K Infinium MethylationEPIC array. Principal component analysis (PCA) was conducted to assess global differences in methylome. cfDNA methylation levels were compared between RC groups using a linear model adjusted for age and sex. PCA suggested differences in methylation profiles between RC groups (p = 0.039) although no significant differentially methylated probes (DMPs; q > 0.15) were found. The top four CpG sites which differed between groups at p < 1E-05 were located in CGGPB1, PEX10, NR0B2, and TP53I11. Gene set enrichment analysis on top DMPs (p < 0.05) showed significant enrichment of gene sets related to nervous system tissues, such as neurons, synapse, and glutamate neurotransmission. Other top notable gene sets were related to parathyroid regulation and calcium signaling. To conclude, our study demonstrated the feasibility of utilizing a microarray method to identify circulating cfDNA methylation sites associated with BD RC and found the top differentially methylated CpG sites were mostly related to the nervous system and the parathyroid.